DFCP1 is a regulator of starvation-driven ATGL-mediated lipid droplet lipolysis - Victoria A. Ismail; Meg Schuetz; Zak N. Baker; Jean A. Castillo-Badillo; Teri V. Naismith; David J. Pagliarini; David J. Kast (Journal of Lipid Research)
Lipid droplets (LDs) are transient lipid storage organelles that can be readily tapped to resupply cells with energy or lipid building blocks, and therefore play a central role in cellular metabolism. Double FYVE Domain Containing Protein 1 (DFCP1/ZFYVE1) has emerged as a key regulator of LD metabolism, where the nucleotide-dependent accumulation of DFCP1 on LDs influences their size, number, and dynamics. Here we show that DFCP1 regulates lipid metabolism by directly modulating the activity of Adipose Triglyceride Lipase (ATGL/PNPLA2), the rate-limiting lipase driving the catabolism of LDs. We show through pharmacological inhibition of key enzymes associated with LD metabolism that DFCP1 specifically regulates lipolysis and, to a lesser extent, lipophagy. Consistent with this observation, DFCP1 interacts with and recruits ATGL to LDs in starved cells, irrespective of other known regulatory factors of ATGL. We further establish that this interaction prevents dynamic disassociation of ATGL from LDs and thereby impedes the rate of LD lipolysis. Collectively, our findings indicate that DFCP1 is a nutrient-sensitive regulator of LD catabolism.